Strategi Pemasaran: Cara Kedai Geprek Niki bisa Bertahan di Era Digital - Fania Alzaira Arrahma; M. Taufiq Abadi (Jurnal Manajemen Riset Inovasi, 2023)
This study aims to analyze the marketing strategy used by Kedai Geprek Niki in facing business competition in the digital era. This study uses qualitative research methods by interviewing the owners and customers of Kedai Geprek Niki. The results show that Kedai Geprek Niki still uses word of mouth marketing as the main method to develop its business. This is done by ensuring quality food and good service to increase customer satisfaction and make them recommend Kedai Geprek Niki to their friends and family. In order to increase customer satisfaction, Kedai Geprek Niki also pays attention to service aspects. They provide special training for their staff to provide good and friendly service to customers. Kedai Geprek Niki also pays attention to aspects of cleanliness and environmental comfort. Based on the results of this study, it can be concluded that Kedai Geprek Niki has managed to survive in the digital era by adopting a marketing strategy that is in line with current business trends. They leverage technology and strengthen their word-of-mouth marketing strategy by focusing on product and service quality.